Theoretical study of aerosol particle electroscavenging by clouds. (September 2019) - Dépée, Alexis; Lemaitre, Pascal; Gelain, Thomas; Mathieu, Anne; Monier, Marie; Flossmann, Andrea
Abstract: This paper describes a theoretical model which computes the collection efficiency of aerosol particles by droplets, due to the combined action of dynamic (inertia, weight and drag) and electrophoresis forces acting on an aerosol particle of radius 0.004 ≤ a ≤ 1.3 μm around a droplet of radius 15 ≤ A ≤ 100 μm . The electrostatic forces are defined following the concept of image charges. In the given particle range, the Brownian motion must be considered and was consequently added to the model. A novel approach is developed, based on the Langevin's theory and solved using an Itô process. Results of electroscavenging related to natural atmospheric ionisation, as well as for strongly charged aerosol particles released after a nuclear accident, are presented with pressure and temperature representative of the mid-troposphere (-17°C, 540 hPa). The droplet charges considered in the paper are representative of weakly and strongly electrified clouds. The values of collection efficiency computed are convenient for incorporation into cloud models and to study scavenging of aerosol particles by clouds whether for climate, pollution or nuclear safety issues. Highlights: Huge impact of the electrostatic forces on the aerosol particle collection by clouds. Enhancement of the collection efficiency sometimes up to four orders of magnitude. Collection efficiency increasing even with repulsive Coulomb inverse square force. Rigorous Lagrangian model implemented for the collection efficiency computation. Collection efficiencies available for few droplet/aerosol particle charges and radii.